Sense of "Calling": An Organizing Principle for the Lives and Values of Young Women in University - French, Jared R.; Domene, Jose F. (Canadian Journal of Counselling and Psychotherapy, 2009)
This qualitative study examined the experience of “life calling” in a sample of female Christian university students who felt a strong sense of calling. Participants were interviewed about the meaning and their experiences of life calling, with thematic analysis revealing the conception of life calling as an organizing and guiding force in these students’ lives, the nature of that calling, the process by which it emerged, and several salient attributes that these individuals had in common. The findings suggest that life calling is a distinct, identifiable phenomenon for some students and may be useful to consider in counselling with these clients.